Increasing Inventory Rating Factor of Steel Truss Bridge Through Orthotropic Steel Deck Panel Application - Erik Wahyu Pradana; Andreas Triwiyono; Ali Awaludin; Saroj Mandal (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2022)
Currently, 18,648 bridges with a total length of 510,366 km have been constructed in Indonesia, but only 86% are in good condition, while the rest are damaged. Steel truss bridge damage generally occurs on the RC decks, and its repair is often implemented through deck replacement or redecking using Orthotropic Steel Deck (OSD) panel. In Indonesia, this method has only been applied limitedly at the Citarum I Bridge in 2009 and the Cisadane Bridge in 2013, while the effect on the existing steel truss bridge is unknown. Therefore, this study aims to evaluate the steel truss bridge performance after OSD panel redecking through numerical modeling. The design process of the OSD panel was carried out by micro-modeling on ABAQUS CAE using shell elements with a mesh size of 50x50 mm and pinned boundary conditions. In this stage, the materials were assumed to be elastic with small deformations. The evaluation of steel truss bridge performance was performed on the A-class steel truss bridge Bina Marga design standard with a 60 m span by comparing the existing bridge inventory rating factor (using RC decks) to OSD panel redecking, which is an indicator of bridge self-weight reduction. Based on the structural macro-model developed using SAP2000, the bridge self-weight reduced the axial tension and compression forces on the steel truss bridge mainframe by 20.6%-24.6% and 20.5%-24.5%, respectively. Consequently, this increased the inventory rating factor by 9.3%-9.5%. In other words, using the OSD panels lighter than the existing RC decks increases the steel truss bridge capacity to resist the live load or vehicle rating throughout its service life.